Cardiovascular risk during early adult life. Risk markers among participants in "Live for Life" health promotion programme in Sweden. Issue 7 (July 1998) - Persson, L G; Lindström, K; Lingfors, H; Bengtsson, C; Lissner, L
Abstract : STUDY OBJECTIVE: To study differences in cardiovascular lifestyle risk factors and biological risk markers in early adult life, with special attention to age and sex differences. Lifestyle cardiovascular risk factors included dietary habits, physical inactivity, smoking, alcohol habits, psychosocial strain, and mental stress. Biological risk markers included anthropometric variables, arterial blood pressure, and serum cholesterol concentration. DESIGN: A combined individual and community based preventive programme, including health examinations. SETTING: All communities in the County of Skaraborg in south western Sweden. PARTICIPANTS: Altogether 12, 982 men and women aged 30 or 35 years who underwent health examinations over seven years. MAIN RESULTS: In both sexes, biological risk markers studied were worse in 35 year old subjects than in 30 year olds. Furthermore, a larger proportion of men aged 35 years were smokers and were physically inactive compared with 30 year old men. However, dietary habits were better in both sexes in the upper age group. At both ages there were also significant differences between men and women. Women, compared with men, had better dietary habits and lower alcohol consumption but smoked more and experienced greater mental stress and psychosocial strain. All biological risk markers were worse in men than in women at both ages studied. During the observation period, some improvement of the health profile of the participants was observed, indicating a beneficial effect of the intervention programme. CONCLUSIONS: The results indicate that the risk of cardiovascular disease, as assessed from studying lifestyle and biological risk markers, increases early in life, suggesting that preventive measures should start early.